2012
DOI: 10.1007/s10729-012-9190-2
|View full text |Cite
|
Sign up to set email alerts
|

Intensity modulated radiation therapy with field rotation—a time-varying fractionation study

Abstract: This paper proposes a novel mathematical approach to the beam selection problem in intensity modulated radiation therapy (IMRT) planning. The approach allows more beams to be used over the course of therapy while limiting the number of beams required in any one session. In the proposed field rotation method, several sets of beams are interchanged throughout the treatment to allow a wider selection of beam angles than would be possible with fixed beam orientations. The choice of beamlet intensities and the numb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 54 publications
(59 reference statements)
0
9
0
Order By: Relevance
“…Treatment information could easily be attached to such a database and previous tumors could be simulated for treatment plans as well. Research [12] has shown that using multiple beam angle sets over a series of treatments has the potential to improve outcomes. Unlike previous work that focused on finding a single best angle set, by sorting, we can find multiple good angle sets; these would allow for a greater distribution of angles to be used with time-varying plans.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment information could easily be attached to such a database and previous tumors could be simulated for treatment plans as well. Research [12] has shown that using multiple beam angle sets over a series of treatments has the potential to improve outcomes. Unlike previous work that focused on finding a single best angle set, by sorting, we can find multiple good angle sets; these would allow for a greater distribution of angles to be used with time-varying plans.…”
Section: Discussionmentioning
confidence: 99%
“…For intensity-modulated x-ray therapy (IMXT), approaches have been developed to allow for a large number of beams in the entire treatment while limiting the number of beams in a single fraction. Dink et al 16 proposed a field rotation method, in which multiple sets of coplanar beams were interchanged between fractions using a mixed integer linear program. Results showed an improvement of dose objectives based on this time-varying method.…”
Section: Introductionmentioning
confidence: 99%
“…IMRT with field rotation was studied in (Dink et al 2012), which first partitions a set of coplanar candidate beams into M disjoint subsets S 1 , …, S M , with each subset consisting of evenly spaced beams, and then assigns one of these M subsets to each treatment fraction. The particular subset that is selected varies from fraction to fraction.…”
Section: Introductionmentioning
confidence: 99%